Design, Fabrication and Testing of Finger-Millet Harvesting Machine - Ghimire, Subodh Kumar; Awal, Rabina; Paneru, Prabin; Bokati, Praveen; Wasti, Sanjita (Journal of the Institute of Engineering, 2019)
Millet harvesting in Nepal is done by conventional method using sickle which is too tedious, time consuming, and inefficient. In this research, a portable millet harvesting machine is designed, fabricated, tested, and its economic analysis is done. This harvesting machine is an approach to solve a real time problem of a millet harvesting. Hence, it can cut earheads and straw separately at a time aimed mainly for the hilly region where a combine harvesting machine is of no use. The machine was tested on small densely planted areas. Machine was able to cut at speed of 1800rpm and power of 0.9kW whereas with decrease in power to 0.7kW and rpm of 1440, cutting was not easy or clear. Manual power was used for motion of wheel, drum and conveyer while cutters were operated by engine power. Due to connection of wheel shaft with drum shaft by chain and sprocket, relatively high manual power was required to push the machine.